Effective salary management: a proposed template / Siti Najihah Abdul Basit ... [et al.] - Abdul Basit, Siti Najihah; Mohd Aris, Aliah Maisarah; Azrol, Nadia Asyura; Abdul Talib, Nur Hanis Nasrin; Johari, Maimunah (Universiti Teknologi MARA, Kedah, 2023)
The purpose of financial planning is to help an individual meet their commitments and realize their goals by considering all aspects of their financial life. Several services, including tax preparation, estate planning, philanthropic planning, and college financial planning, might be included. Assessing existing financial circumstances, establishing reasonable goals, and developing plans to achieve those targets are all essential components of effective financial planning. Planning, savings, investment planning, risk management, tax optimization, and retirement planning are just a few of the many topics it handles. Individuals can overcome financial difficulties, make wise decisions, and make the most of their financial resources by creating a thorough financial plan. Nowadays, people tend to overspend their money to follow the trend and buy something that is not necessary for their daily life. To achieve good financial planning, we must start managing our finances wisely according to our basic salaries. We manage our salaries to minimize debt. Debts like credit cards and personal finance, the short-term effect is fun because you can spend on the things you want even if the income is not enough. But, in the long run, these debts can have a detrimental effect on one's financial position. The 30/10 formula involves dividing the salary into 4 parts, namely 30%, 30%, 30%, and 10%. The 30/10 formula, which balances the four key components of personal financial management such as savings, expenses, protection, and investment can be considered the best salary money management formula. The right balance between the inflow and outflow of funds will be assisted by financial planning. It enables the person or organization to adjust their plan in response to shifting market conditions.